TThe Effect of Occupational Health and Safety Education on Improving The Quality of The Learning Environment - Asrul Asrul; Rudi Purwana (International Archives of Medical Sciences and Public Health, 2022)
A safe and healthy learning environment plays an important role in improving the quality of education. This study aims to explore the effect of occupational health and safety education on improving the quality of the learning environment in schools. The research method used was a survey involving 200 respondents from 10 secondary schools in urban areas. The data was collected using a questionnaire consisting of structured questions about health education, work safety and the quality of the learning environment. Data analysis was performed using multiple linear regression techniques. The results showed that there was a positive and significant relationship between occupational health and safety education and improving the quality of the learning environment (p <0.05 ). These findings indicate that health education efforts that are integrated with work safety can contribute to improving the quality of the learning environment in schools. The discussion highlights the important role of occupational health and safety education in creating a learning environment that is safe, healthy and supports an effective learning process. Improving the quality of the learning environment can have a positive impact on student welfare, academic performance, and active participation in the educational process. Therefore, it is important for schools and policy makers to prioritize occupational health and safety education as an integral part of the education system.